2010
DOI: 10.26719/2010.16.supp.61
|View full text |Cite
|
Sign up to set email alerts
|

Creating synergies for health systems strengthening through partnerships in Pakistan - a case study of the national eye health programme

et al.

Abstract: Blindness and visual impairment are major causes of noncommunicable diseases in Pakistan. Two national population-based blindness surveys conducted in 1988 and 2002-04 demonstrated a reduction in prevalence of blindness from 1.78% to 0.9% with a significant drop in cataract blindness as a result of accelerated nationwide interventions and eye care integration in primary health care. In addition, between 2006 and 2008, 88 facilities were upgraded as a result of the national eye health programme. These measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Four papers described the importance of health systems strengthening with regards to eye health [55-57,72,73]. Table 1 shows that most of the 173 papers included in this review, 43 of which are reviews, contain information from sub-Saharan Africa (76) or from low- and middle-income countries (47).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four papers described the importance of health systems strengthening with regards to eye health [55-57,72,73]. Table 1 shows that most of the 173 papers included in this review, 43 of which are reviews, contain information from sub-Saharan Africa (76) or from low- and middle-income countries (47).…”
Section: Resultsmentioning
confidence: 99%
“…There is however insufficient evidence to show improvements in outcomes in patients with multi-morbidity in primary care and community settings [132]. The eye health program in Pakistan reported some challenges in aligning eye health with the national health systems, but attributes the success of their program to their health systems strengthening approach and integration into primary health care [73]. …”
Section: Resultsmentioning
confidence: 99%
“…Also in India, in Orissa, a leprosy programme was integrated into general care without impact on quality or effectiveness 59. In Pakistan, blindness prevention was gradually and successfully integrated into routine primary care over an extended period; and in the Philippines, diabetes prevention and management were integrated into the work of existing staff yielding positive clinical outcomes 60. Facilitators of integration included strong health managers, provider engagement, and careful planning and co-ordination.…”
Section: Resultsmentioning
confidence: 99%
“…The study of a gatekeeping trial reported reduced hospital utilisation, but noted PHC infrastructure enhancements were needed to attract patients. Other studies found that contracting services to non-state providers offered savings by reducing the cost of delivering care mainly due to better administrative, managerial and absorptive capacity among these providers 60 63–65. The importance of contract management skills in government, and trust between government and providers, were highlighted as a critical factors.…”
Section: Resultsmentioning
confidence: 99%
“…Visual impairment and blindness are two significant problems associated with public health[ 1 2 3 ] because they can affect the lives of individuals, families, and societies. [ 4 ] The most important effects of visual impairment and blindness are negative health consequences (increase in mortality rate and reduction in quality of life)[ 2 5 6 7 8 ] and negative social-economic implications (loss of employment, economic power, and productivity).…”
Section: Introductionmentioning
confidence: 99%